THE ANALYSIS OF IAIN PAREPARE STUDENTS’ ACADEMIC WRITING LEVELS ON IELTS PREPARATION CLASS - Revit Rendra Wicaksono; Nurhamdah Nurhamdah; Kalsum Kalsum (Al-Irsyad: Journal of Education Science, 2023)
This research is intended to describe the academic writing levels of 13 EFL students at IAIN Parepare and to consider what is the students’ perceptions are about IELTS academic writing levels after finishing the IELTS Preparation class. The researcher used qualitative descriptive method. The researcher collected the students’ worksheet and assessed based on IELTS writing band score descriptors that consists of four aspects writing assessment criteria: task achievement and response, coherence and cohesion, lexical resource, grammatical range and accuracy. To gain information about students’ perception, the researcher guided an interview.The result found that 2 students achieved 7 band scores (Good User Level) as the highest achiever. Then, 2 students achieved 5,5 band scores (Modest User Level) as the medium achievement, and only 1 student achieved 3 band score (Extremely Limited User level) as the lowest achiever. The researcher chose three selected texts were written by MA who represents the lowest level of achievement, NQA who represents medium level achievement, and SHB who represents the highest level of achievement. The results showed that the essays mostly had difficulty in grammatical range (accuracy) and lexical resources, both in task 1 and task 2. Furthermore, the students assumed that the IELTS academic writing level/task were difficult. The students’ difficulties appear in vocabulary and grammar. The students’ difficulties appear in vocabulary and grammar. Achieving expert user level was difficult because English was not their first language. Also, it was the first time for them to introduce the IELTS test.